Collar Manufacturing Process With Turret Machine - Muhammad Yusuf Nurfani (International Journal of Mechanical, Industrial and Control Systems Engineering, 2024)
The turret machine is one type of lathe that has The main characteristic is that the tool for sequential operations can be set in readiness for use in the appropriate sequence. This turret machine is intended for cutting, drilling and smoothing work pieces. The process of making this collar aims to find out what material is used and the function of the collar. In the process, the iron is clamped with a chuck then the drill which is located on the loose head is brought close to the workpiece then the chuck rotates so that the workpiece has a hole with an inner diameter of 11.2 mm, after that the workpiece is sprayed with bromus liquid to ensure that the workpiece does not rust easily and does not experience excessive heat which can damage the workpiece. Entering the next stage, the workpiece is cut to a length of 9 mm, and the next process is that the workpiece is placed in a jumper. The cumper process functions to smooth the workpiece so that it is not rough before entering quality control. After that, the object enters quality control. In quality control, the work object is measured using a jig measuring tool to determine whether the work object is OK or NG. The aim of this process is to make quality spare parts that are safe to use. The disadvantage of the turret machine is that it is a manual process that requires hand speed and expertise in operating the turret machine..